2020
DOI: 10.1093/infdis/jiaa399
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Induced Macrophage-Derived Exosomes Mediate Antiviral Activity Against Hepatitis B Virus Through miR-574-5p

Abstract: Background Interferon alpha (IFN-α) has been proven effective in treating chronic hepatitis B (CHB) due to its capability to suppress hepatitis B surface antigen (HBsAg) and hepatitis B virus (HBV) covalently closed circular DNA (cccDNA). However, the underlying mechanisms are blurred. Methods We investigated the antiviral activities of exosomes from responders and non-responders to pegylated IFN-α (PegIFN-α) as well as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…These IFN-α-related exosomal miRNAs, including miR-25, miR-193 and miR-574, can suppress HBV replication by degrading HBV DNA. Importantly, no change in three IFN-α-related miRNAs was observed in IFN nonresponders (Wu et al 2020) (Table 2). These results suggest that some exosomal miRNAs may be involved in the induction of abnormal immunity by HBV, while some promote the antiviral effects of IFN-α.…”
Section: Roles Of Exosomal Mirnas and Proteins During Hbv Infectionmentioning
confidence: 95%
See 1 more Smart Citation
“…These IFN-α-related exosomal miRNAs, including miR-25, miR-193 and miR-574, can suppress HBV replication by degrading HBV DNA. Importantly, no change in three IFN-α-related miRNAs was observed in IFN nonresponders (Wu et al 2020) (Table 2). These results suggest that some exosomal miRNAs may be involved in the induction of abnormal immunity by HBV, while some promote the antiviral effects of IFN-α.…”
Section: Roles Of Exosomal Mirnas and Proteins During Hbv Infectionmentioning
confidence: 95%
“…Therefore, it is presumed that some of the miRNAs that are enriched in exosomes can impair the innate immune response by targeting the proinflammatory cytokines degradation in the context of HBV infection. However, a recent study showed that some exosomal miRNAs are increased both in CHB patients who are IFN responders and in THP-1 macrophages (Wu et al 2020). These IFN-α-related exosomal miRNAs, including miR-25, miR-193 and miR-574, can suppress HBV replication by degrading HBV DNA.…”
Section: Roles Of Exosomal Mirnas and Proteins During Hbv Infectionmentioning
confidence: 99%
“…Furthermore, macrophage derived exosomes facilitate antiviral activity during chronic HBV infection through miR-574-5p. Exosomes treated with pegylated interferon-α (PegIFN-α) exhibited anti-HBV activities including the suppression of HBsAg, HBeAg, HBV DNA, and covalently closed circular DNA (cccDNA) levels in HBV cell lines, suggesting exosomes can transport IFN-α related miRNAs from macrophages to HBV-infected hepatocytes [ 139 ]. Treatment with PegIFN-α upregulated exosomal hsa-mir-193a-5p, hsa-miR-25-5p, and hsa-miR-574-5p that partially inhibited HBV replication and transcription.…”
Section: Innate and Adaptive Immune Response Against Hbv Infectionmentioning
confidence: 99%
“…Beyond the scope of a single cell, cell-to-cell transmission of viral resistance is also a mechanism for amplifying IFN-ainduced antiviral response. IFN-a can induce the transfer of resistance to HBV from nonpermissive liver nonparenchymal cells (LNPCs) to hepatocytes via exosomes (39)(40)(41). Exosomes from IFN-a-treated LNPCs are rich in molecules with antiviral activity.…”
Section: Advantages and Mechanisms Of Ifn-a Treatment Against Chbmentioning
confidence: 99%